Palmitic acid promotes endothelial-to-mesenchymal transition via activation of the cytosolic DNA-sensing cGAS-STING pathway - Liu, Qian; Cheng, Zhe; Huang, Bi; Luo, Suxin; Guo, Yongzheng (Archives of biochemistry and biophysics, 2022)
Elevated levels of plasma free fatty acids (FFAs) lead to endothelial dysfunction, a process that is involved in the pathogenesis of atherosclerosis. Endothelial-to-mesenchymal transformation (EndMT) has been reported to accelerate endothelial dysfunction during the process of atherosclerosis. However, the underlying mechanisms of EndMT remain poorly understood. The present study aimed to investigate the role of the cytosolic DNA-sensing cyclic GMP-AMP synthase-stimulator interferon gene (cGAS-STING) pathway in palmitic acid (PA)-induced EndMT. Human aortic endothelial cells (HAECs) were exposed to different concentrations of PA, and subsequently its effects on EndMT and the cGAS-STING pathway were assessed. To investigate the role of cGAS-STING pathway on PA-induced EndMT, RNA interference was used to knockdown the expression of cGAS in HAECs prior to their exposure to PA. First, it was observed that PA reduced cell viability and intracellular nitric oxide production, and increased migratory capacity of the HAECs as well as the cellular oxidative stress response, leading to EndMT. Moreover, it was observed that the cGAS-STING pathway was activated in PA-exposed primary HAECs. Activating cGAS-STING pathway via mtDNA directing lead to EndMT in HAECs. Interestingly, cGAS knockdown by RNA interference attenuated PA-induced inflammation, oxidative stress and EndMT in HAECs. Taken together, the results of the present study suggested that the cytosolic DNA-sensing cGAS-STING pathway may have important roles in PA-induced EndMT in endothelial cells.